The effectiveness of schema therapy on the quality of life of adolescent girls with borderline personality disorder - Zamani, Mina; Sotodehasl, Nemat; Makvand Hosseini, Shahrokh; Sabahi, Parviz (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to determine the effectiveness of schema therapy on quality of life in adolescents with borderline personality disorder. Methods: The present study was a real experimental factor design with pre-test and post-test with a 2-month follow-up phase. The statistical population of the present study included all adolescent female patients in the age range of 15 to 17 and with borderline syndrome disorder in Bojnourd public ward transplant clinic in 1399-1400. Using simple random sampling method, 40 of them were selected and 3 experimental groups (10 people in each group) and one control group (10 people) were replaced. The experimental groups underwent 20 sessions of 90-minute schema therapy with cognitive, experimental and behavioral techniques; But the control group did not receive any intervention and remained on the waiting list. The Borderline Personality Traits Scale for Children (BPFS-C) of Craig et al. (2005) and the Quality of Life Questionnaire (SF-36) by War and Chorbon (1992) were used to collect data. The analysis of the information obtained from the implementation of the questionnaires was performed through SPSS software version 24 in two descriptive and inferential sections (analysis of variance with repeated measures and Ben Foroni post hoc test). Results: The results showed that the mentioned treatment with its three techniques in the post-test and follow-up stage compared to the control group had a significant effect on increasing the quality of life of borderline personality (P <0.05). Conclusion: Based on the results of the present study, it can be said that schema therapy can be used as a treatment method to increase the quality of life of borderline personality of adolescent girls with borderline personality disorder in medical centers.